2023
DOI: 10.3390/ijerph20042920
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Fear after an Anterior Cruciate Ligament Injury: A Qualitative Thematic Analysis Using the Common-Sense Model

Abstract: Fear is a significant factor affecting successful return to sport following an anterior cruciate ligament (ACL) injury. However, there is a lack of understanding of the emotional drivers of fear and how fear beliefs are formed. This study qualitatively explored the contextual and emotional underpinnings of fear and how these beliefs were formed, with reference to the Common-Sense Model of Self-Regulation. Face-to-face online interviews were conducted with ACL-injured participants (n = 18, 72% female) with a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 68 publications
0
4
0
2
Order By: Relevance
“…Patients’ descriptions of feelings include: burden, worry, frustration, hopelessness, devastation, and isolation. 23,30,36,52,68 Mental health conditions, such as anxiety and depression, may increase in severity in response to injury and be detrimental to outcomes. 46 Schaffer et al 58 observed outcomes of patients stratified into 3 cohorts: clinical diagnosis of depression, situational depression, and no depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients’ descriptions of feelings include: burden, worry, frustration, hopelessness, devastation, and isolation. 23,30,36,52,68 Mental health conditions, such as anxiety and depression, may increase in severity in response to injury and be detrimental to outcomes. 46 Schaffer et al 58 observed outcomes of patients stratified into 3 cohorts: clinical diagnosis of depression, situational depression, and no depression.…”
Section: Discussionmentioning
confidence: 99%
“…Further, diminished mobility often affects social interactions, shifting perception and expectations among friends and strangers. 23,30 Patients may reevaluate their lives, choosing family, work, and education commitments as greater priorities. 23,33 Psychosocial Influences on RTS It is understood that the criteria for RTS is inconsistent.…”
Section: Impact Of Injury Experiencementioning
confidence: 99%
“…Die erfolgreiche Rückkehr zum Sport scheint eng mit der Reduktion maladaptiver, protektiver Bewegungsmuster sowie der Genesungserwartung, der mentalen Gesundheit und der funktionellen Leistungsfähigkeit verknüpft zu sein [7][23] [25]. Für den Übertrag auf die Praxis ist es daher wichtig zu verstehen, dass sich physische, psychische, soziale und kontextuelle Faktoren gegenseitig beeinflussen und somit im Reha-Prozess mitbetrachtet werden müssen [17] [18].…”
Section: Reha Nach Kreuzbandruptur: Rückkehrbereitschaft In Den Sport...unclassified
“…In comparison to the vast body of quantitative work, there are few qualitative studies investigating the experiences of individuals following ACL injury, and most focus on experiences related to rehabilitation, return to sport and fear of reinjury 12–21. We could only find one study which investigated individuals’ perceptions of QOL after ACL injury, however, this study was conducted after participants had undergone ACL reconstruction 22.…”
Section: Introductionmentioning
confidence: 99%